2010
DOI: 10.1371/journal.pntd.0000652
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Clustering of Porcine Cysticercosis in Mbulu District, Northern Tanzania

Abstract: BackgroundPorcine cysticercosis is caused by a zoonotic tapeworm, Taenia solium, which causes serious disease syndromes in human. Effective control of the parasite requires knowledge on the burden and pattern of the infections in order to properly direct limited resources. The objective of this study was to establish the spatial distribution of porcine cysticercosis in Mbulu district, northern Tanzania, to guide control strategies.Methodology/Principal FindingsThis study is a secondary analysis of data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 17 publications
(36 reference statements)
3
44
1
Order By: Relevance
“…The 2012 National Census showed a population of 320,279 people comprised of 161,548 men and 158,731 women with an average of 6 people per household. Crop and livestock production are the most important economic activities, employing more than 90% of the total labour force (Ngowi et al, 2010).…”
Section: Study Areamentioning
confidence: 99%
“…The 2012 National Census showed a population of 320,279 people comprised of 161,548 men and 158,731 women with an average of 6 people per household. Crop and livestock production are the most important economic activities, employing more than 90% of the total labour force (Ngowi et al, 2010).…”
Section: Study Areamentioning
confidence: 99%
“…It has been suggested that a study area's boundary extent can affect the likelihood for detecting a true cluster (Jacquez and Greiling, 2003;Wheeler, 2007). Papers in our review illustrate this effect, which detected clusters that span several km in diameter throughout a rural area (Ngowi et al, 2010), or multiple contiguous neighbourhoods throughout a metropolitan area (Chaix et al, 2006). Our method test with pedestrian injury illustrated this particular effect when applying the spatial scan statistic to the same dataset only changed by an increased sample size and study area size (Fig.…”
Section: Aetiologymentioning
confidence: 60%
“…The primary use of K-function analysis was exploring the presence and scale of spatial clustering of the selected exposure variables (Austin et al, 2005;Hillier et al, 2009;Day and Pearce, 2011). The K-function was also used to assess the spatial structure of a distribution before conducting local analyses of spatial clustering (Han et al, 2004;Broman et al, 2006;Wheeler, 2007;Epp et al, 2010;Ngowi et al, 2010;Poljak et al, 2010). Knowing the scale and structure of the spatial dependency among data helps the user confirm whether local analyses are required as well as provide an approximation of spatial weight specifications.…”
Section: K-functionmentioning
confidence: 99%
See 2 more Smart Citations